The 10th Flora Malesiana Symposium - Wilkie, Peter (Sibbaldia: the International Journal of Botanic Garden Horticulture, 2018)
The 10th Flora Malesiana Symposium was held at the Royal Botanic Garden Edinburgh (RBGE) between 11 and 15 July 2016 and was attended by 185 researchers from 25 countries. Over five days, taxonomists, horticulturists and conservationists came together to present and discuss their research on the plant diversity of the Malesian region. Over 160 presentations were given and a series of very popular workshops was run.